Partition-based approach to parametric dynamic compact thermal modeling. (December 2017) - Codecasa, Lorenzo; d'Alessandro, Vincenzo; Magnani, Alessandro; Rinaldi, Niccolò; Metzger, Andre G.; Bornoff, Robin; Parry, John
Abstract: This paper presents three procedures for the extraction of parametric Dynamic Compact Thermal Models (DCTMs) with controlled and user-chosen accuracy, namely, (i) a DCTM with dense matrices obtained by a direct conventional method, (ii) a partition-based approach leading to a sparse DCTM suited for heat conduction problems suffering from a massive number of independent heat sources and/or parameters, for which extracting conventional dense DCTMs may be too resource-demanding or even unviable, and (iii) a novel algorithm that quickly translates a sparse DCTM into a dense one, which allows reducing the simulation time. The proposed methodologies are validated through the application to two state-of-the-art electronics systems. Highlights: Fast MOR algorithms are proposed for parametric dynamic compact thermal models (DCTMs). Sparse DCTMs are conceived to lower the extraction effort due to many heat sources. All the proposed algorithms for DCTM extraction feature tight guaranteed error bounds. DCTMs outperform standard numerical methods in terms of drastically lower CPU time. IGBT power module and HBT output array were considered as realistic case studies.